LAW ENFORCEMENT OF ADOLESCENT DELIVERY IN THE PERSPECTIVE OF CHILDREN'S LAW BASED ON RESTORATIVE JUSTICE - Samsuria Samsuria; Heru Wardoyo (Omnibus Law Journal, 2022)
In law enforcement efforts related to juvenile delinquency in terms of the perspective of the Children's Law, it is necessary to pay attention together so that the settlement of these crimes can be resolved through channels outside the judiciary so that the mental and the psychology of the child or teenager can be minimized. Restorative justice is present not only to provide space for the settlement of crimes involving children outside the Judiciary, but also to seek solutions that promote a sense of justice through deliberation, etc. This type of research is normative legal research, the emphasis of normative legal research lies in legal studies, or legal studies (rechtsboefening) on ​​positive law, which includes two layers of legal scholarship, consisting of legal dogmatic studies and legal theory studies. Keywords: Law Enforcement, Youth, Restorative Justice